THE IMPLEMENTATION OF EGRA (EXPOSURE, GENERALIZATION, REINFORCEMENT AND APPLICATION) TECHNIQUE TO REDUCE STUDENTS’ GRAMMATICAL ERRORS - Bukan, Fransiska Lasa; Alinda, Marta (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
This study aimed to address the challenge of English grammar learning for eighth-grade students at SPNF SKB SIKKA, employing the EGRA technique in a classroom action research (CAR) format. Data, gathered through observation sheets, interviews, and tests, were analyzed quantitatively and qualitatively. In the initial cycle, students demonstrated low engagement and reported difficulties with unclear explanations. Quantitative analysis revealed significant grammatical errors, notably in Mis-formation (26.11%). Following the EGRA technique in the second cycle, improvements were observed, with the highest error in Mis-formation (31.43%) and an increased average score of 70.33. Qualitative findings indicated enhanced classroom conditions and student understanding. The study concludes that the EGRA technique effectively reduces grammatical errors, suggesting its viability as an innovative tool for teaching the simple present tense